2019
DOI: 10.1088/1361-6501/ab39b4
|View full text |Cite
|
Sign up to set email alerts
|

A low-temperature Kerr effect microscope for the simultaneous magneto-optic and magneto-transport study of magnetic topological insulators

Abstract: Magneto-optical Kerr effect (MOKE) microscopy is a surface-sensitive probe of magnetisation with micron-sized lateral resolution. Here, we present a low-temperature, focused polar MOKE microscope for the simultaneous magnetooptical and magneto-transport measurements, which has a temperature range of 1.6-300 K and is equipped with a magnet capable of delivering a field of up to 9 T. In this microscope, all optical components are integrated in a free-standing probe, allowing for the straightforward incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…We found that V works as a surfactant which undesirably prevents the substitutional doping of Cr into Sb sites, leading to the formation of the secondary phase Cr 2 Te 3 . [145,179] Apart from co-doping, the other highlighted approach to QAH insulators is modulation doping in heterostructures, [30] that is, periodically inserting a doped Cr:BST layer during the growth of non-doped BST films, a technique that had been applied to GaAs/Al x Ga 1−x . As semiconductor heterostructures to achieve a high carrier mobility.…”
Section: Magnetic-doped Quantum Anomalous Hall Insulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that V works as a surfactant which undesirably prevents the substitutional doping of Cr into Sb sites, leading to the formation of the secondary phase Cr 2 Te 3 . [145,179] Apart from co-doping, the other highlighted approach to QAH insulators is modulation doping in heterostructures, [30] that is, periodically inserting a doped Cr:BST layer during the growth of non-doped BST films, a technique that had been applied to GaAs/Al x Ga 1−x . As semiconductor heterostructures to achieve a high carrier mobility.…”
Section: Magnetic-doped Quantum Anomalous Hall Insulatorsmentioning
confidence: 99%
“…In this example, SQUID-on-tip microscopy images show the out-of-plane component of the magnetic stray field of a Cr:BST sample at 250 mK, in an opposite applied magnetic field of ≈300 mT, that is, the reversal of the magnetic domains is visible. c) MOKE is a surface-sensitive technique with a lateral resolution of ≈μm, which can be easily integrated within a cryostat [145]. d) XMCD and XMLD, which are carried out at synchrotrons, rely on the magnetic field or polarization-dependent XAS spectra and allow for the element-selective probing of the different forms of magnetic order.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such behavior is caused mainly by the interferences between the layers, as the optical properties of thin Cr layers (below 20 nm) are found to be typical of dielectric materials. This could be of interest for the development of optical microscopy [23] and sensing [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the temperature dependence of the exchange bias in the superlattice, we conducted polar MOKE experiments using the geometry shown in Figure 3 a, 17 where a linearly polarized laser beam is perpendicularly incident on the sample and reflected with a small polarization rotation angle. The experimental procedure follows the step-by-step diagram shown in Figure 3 b.…”
mentioning
confidence: 99%